2021
DOI: 10.3390/ani11061492
|View full text |Cite
|
Sign up to set email alerts
|

Excavation of Genes Related to the Mining of Growth, Development, and Meat Quality of Two Crossbred Sheep Populations Based on Comparative Transcriptomes

Abstract: Crossbreeding can improve production performance and meat quality in sheep. The objective of this study was to look for genes related to sheep growth, development, and muscle. In this study, Dorper (DP) × Small Tailed Han (STH) sheep and Mongolia (MG) × Small-tailed Han (STH) sheep were used to estimate the productive performance and meat quality in a crossbreed. Subsequently, transcriptome analysis and bioinformatic analysis were performed on the Longissimus dorsi muscles of DP × STH and MG × STH sheep to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…Meanwhile, it is an early maturing and fat depositing breed with a high average daily gain ( Brand et al, 2017 ). Many studies on improving the growth of indigenous breeds by crossing them with Dorper have been reported ( Weldeyesus, 2017 ; Shi et al, 2021 ). As a remarkable local breed in China, the Small-tailed Han sheep (STH) has a significant characteristic of high fecundity ( Wang et al, 1990 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it is an early maturing and fat depositing breed with a high average daily gain ( Brand et al, 2017 ). Many studies on improving the growth of indigenous breeds by crossing them with Dorper have been reported ( Weldeyesus, 2017 ; Shi et al, 2021 ). As a remarkable local breed in China, the Small-tailed Han sheep (STH) has a significant characteristic of high fecundity ( Wang et al, 1990 ).…”
Section: Introductionmentioning
confidence: 99%
“…We focused on the GO terms related to sheep meat quality, as these characteristics are the main factors that affect the performance of domestic animals. Finally, the DEGs enriched in these GO terms were selected as the target DEGs for further analysis [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…A denaturation step was performed for one cycle at 95°C for 30 s. The annealing step was run for 40 cycles at 95°C for 5 s and 60°C for 31 s. All PCR were performed in triplicates. The results were calculated using the 2 −ΔΔCT method [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…Using FDR < 0.01 and |log2FC|>1 as the standard ( 15 , 23 ) DEGs were screened, following which DEGs were annotated and enriched through the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). We selected the DEGs from the GO terms and pathways including the keywords such as development, growth, muscle, which were involved in sheep production performance and meat quality according to previous studies ( 6 , 7 , 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…Liu et al ( 12 ) used RNA-Seq technology to study the miRNAs of prenatal and postpartum skeletal muscles of sheep, and performed screening of a total of 1126 miRNAs, of which 40 were new candidate miRNAs, following which they confirmed that the development of skeletal muscle was related to the targeted genes of miRNA. Shi et al ( 13 ) conducted a transcriptome analysis and comparison of the longissimus dorsi muscle of different sheep and performed screening of 1,445 DEGs, of which 199 were related to growth and development and 43 were key genes related to meat quality traits. Zhan et al ( 14 ) performed whole transcriptome sequencing using the longissimus dorsi muscle tissue of sheep in the prenatal and neonatal stages and identified 3276 DEGs, which were found to be significantly enriched in 22 pathways.…”
Section: Introductionmentioning
confidence: 99%